Transition pathways out of pediatric care and associated HIV outcomes for adolescents living with HIV in South Africa - Haghighat, R; Toska, E; Cluver, L; Gulaid, L; Mark, D; Bains, A (Lippincott, Williams and Wilkins, 2019)
BACKGROUND:Research on adolescent transitions out of pediatric HIV care has focused on high-income countries, with limited understanding of transitions in sub-Saharan Africa's public health sector. METHODS:Patient file data was extracted through December 2017 for all 10- to 19-year-olds ever initiated on ART in a health district of the Eastern Cape, South Africa (n=951). Pathways in HIV care were identified by tracing movements across facility care types and levels. Associations between pathways and viral failure, mortality, loss to follow-up, and viral load change were tested in sequential multivariable regressions. Analyses controlled for sociodemographic and treatment-related variables. Thematic analyses of semi-structured healthcare provider interviews identified transition support at included facilities. RESULTS:Only 57.8% of adolescents had initiated ART in pediatric care, and 20.4% of the total cohort had transitioned out of pediatric HIV care. Among the 42.2% who had initiated in non-pediatric care, 93.8% remained exclusively in non-pediatric care. Median age at first transition was 14 years. Two main pathways were identified: classical transition to adult HIV care (43.3%) and down-referral transition to primary healthcare clinics (56.7%). Across pathways, 27.3% experienced cyclical transition, or repeated movement between pediatric and non-pediatric care. Independent of covariates, adolescents with down-referral transition were less likely to demonstrate viral failure (AOR 0.21 [95%CI 0.10-0.42], p<0.001). Mortality and loss to follow-up were not associated with either pathway. Median post-transition viral load change was not clinically significant (0.00 [IQR: 0.00-0.35]) or associated with transition pathways. Healthcare providers described informal "protocols" for mitigating risk of negative post-transition HIV outcomes. CONCLUSIONS:This study proposes a contextually relevant model for transitions out of pediatric HIV care in South Africa. Feasible, scalable "protocols" may mitigate risk of worsening post-transition HIV outcomes.